2009
DOI: 10.1136/hrt.2009.178178
|View full text |Cite
|
Sign up to set email alerts
|

Brief low-workload myocardial ischaemia induces protection against exercise-related increase of platelet reactivity in patients with coronary artery disease

Abstract: A short episode of myocardial ischaemia induces protection against an exercise-induced increase of platelet reactivity. These data also suggest a role for adenosine in this phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
2
10
0
1
Order By: Relevance
“…Taken together with the previous study by the same group,16 we now have evidence regarding the equal effectiveness of RIPC and that of local IPC on the platelet activation pathway. RIPC is an attractive treatment modality, and this is probably the way to go; indeed, it is the focus of current clinical studies.…”
supporting
confidence: 80%
“…Taken together with the previous study by the same group,16 we now have evidence regarding the equal effectiveness of RIPC and that of local IPC on the platelet activation pathway. RIPC is an attractive treatment modality, and this is probably the way to go; indeed, it is the focus of current clinical studies.…”
supporting
confidence: 80%
“…In patients with CAD, even low levels of physical exercise have been shown to transiently increase platelet aggregability, which might result in coronary occlusion in case of plaque rupture 107. Scalone et al demonstrated that a short episode of myocardial ischemia in symptomatic patients with CAD (induced by an exercise bout at low work load and stopped at 1‐mm ST‐segment depression) protected these patients from an increase in platelet reactivity in a subsequent maximum exercise stress test 108. Remote upper arm ischemic conditioning resulted in comparable protective effects on platelet reactivity 109.…”
Section: Mechanism 5: Platelet Activationmentioning
confidence: 99%
“…13,37 Importantly, although no experimental studies have assessed the effect of remote IPC on platelet function, recent data show that remote IPC is able to blunt platelet activation associated with myocardial ischemia. 11,12 In the present study, we provide evidence that remote IPC, induced by intermittent forearm ischemia, is also able to significantly reduce platelet activation and reactivity during radiofrequency ablation of AF and that its antiplatelet effect persists up to 24 hours after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…32 Subsequent studies showed that IPC can also be induced by the application of short episodes of ischemia in peripheral tissues, typically in the forearm, a phenomenon defined as remote IPC. 9,10 In the clinical setting, remote IPC has been shown to limit myocardial suffering and damage after transient ischemic episodes 13 or persistent thrombotic coronary occlusion. 33 Although the clinical benefits of IPC are largely related to some favorable changes in myocardial cells that make them more resistant to ischemic injury, a few studies suggested that IPC can also induce other beneficial pathophysiological effects, including a reduction in platelet reactivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation